2020
DOI: 10.2147/cmar.s278902
|View full text |Cite
|
Sign up to set email alerts
|

<p>LCN2 Mediated by IL-17 Affects the Proliferation, Migration, Invasion and Cell Cycle of Gastric Cancer Cells by Targeting SLPI</p>

Abstract: Introduction Gastric cancer occurred in China and even the whole East Asia with high incidence. The objective of this study was to investigate the role of IL-17 in gastric cancer cells mediated by LCN2 binding to SLPI . Methods The expression of LCN2 and SPLI in gastric cancer cells and transfection effects were confirmed by RT-qPCR anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Previous studies have shown that high LCN2 expression levels were correlated with poor prognosis in breast cancer patients [ 17 , 25 , 26 , 27 ]. We further validated these findings by analyzing a meta‐dataset of 8951 breast cancers, in which 87% of tumor samples were classified as LCN2 ‐low ( n = 7830/8951) and 13% as LCN2 ‐high ( n = 1121/8951).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that high LCN2 expression levels were correlated with poor prognosis in breast cancer patients [ 17 , 25 , 26 , 27 ]. We further validated these findings by analyzing a meta‐dataset of 8951 breast cancers, in which 87% of tumor samples were classified as LCN2 ‐low ( n = 7830/8951) and 13% as LCN2 ‐high ( n = 1121/8951).…”
Section: Resultsmentioning
confidence: 99%
“…LCN2 has been implicated in the progression of several types of human tumors. LCN2 expression is higher in solid tumors than in corresponding normal tissues [ 25 , 41 ], and it is mainly described as tumor promoter in many cancers, including pancreas, glioblastoma, thyroid, kidney, esophagus, and breast cancer [ 19 , 28 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study 43 showed that the median serum IL-17 level in GC patients was signi cantly higher than that in controls (9.04 VS 8.07 pg/ml, p=0.01), which shows that serum IL-17 level can be used as a new potential indicator for GC diagnosis. Xu J et al 44 found that IL-17-mediated downregulation of LCN2 expression inhibited the proliferation, migration, and invasion of GC cells by regulating SLPI. In addition to IL-17A, a member of the IL-17 family, several experiments have con rmed that IL-17B/IL-17 receptor B (IL-17RB) can inhibit growth and progression of tumor.…”
Section: Ingredients and Targets Analysismentioning
confidence: 99%